Automatic multi-direction slicing algorithms for wire based additive manufacturing. (February 2016) - Ding, Donghong; Pan, Zengxi; Cuiuri, Dominic; Li, Huijun; Larkin, Nathan; van Duin, Stephen
Abstract: One of the key challenges in Additive Manufacturing is to develop a robust algorithm to slice CAD models into a set of layers which requires minimal support structures. This paper reports the concept and implementation of a new strategy for multi-direction slicing of CAD models represented in STL format. Differing from the existing multi-direction slicing approaches that are mainly focused on finding an optimal volume decomposition strategy, this study presents a decomposition-regrouping method. The CAD model is firstly decomposed into sub-volumes using a simple curvature-based volume decomposition method. Then a depth-tree structure based on topology information is introduced to merge them into ordered groups for slicing. In addition, a model simplification step is introduced before CAD model decomposition to significantly enhance the capability of the proposed multi-direction strategy. The proposed strategy is shown to be simple and efficient on various tests parts especially for geometries with large number of holes. Highlights: Multi-direction slicing algorithms are developed for wire based additive manufacturing. A new strategy of volume decomposition-regrouping is reported. Model simplification (hole-filling) is performed to simplify CAD models. The proposed strategy is simple and efficient.